The flight of physicians from West Africa: Views of African physicians and implications for policy - Hagopian, A.; Ofosu, A.; Fatusi, A.; Biritwum, R.; Essel, A.; Hart, L.G.; Watts, C. (Social Science and Medicine, 2005)
West African-trained physicians have been migrating from the sub-continent to rich countries, primarily the US and the UK, since medical education began in Nigeria and Ghana in the 1960s. In 2003, we visited six medical schools in West Africa to investigate the magnitude, causes and consequences of the migration. We conducted interviews and focus groups with faculty, administrators (deans and provosts), students and post-graduate residents in six medical schools in Ghana and Nigeria. In addition to the migration push and pull factors documented in previous literature, we learned that there is now a well-developed culture of medical migration. This culture is firmly rooted, and does not simply fail to discourage medical migration but actually encourages it. Medical school faculty are role models for the benefits of migration (and subsequent return), and they are proud of their students who successfully emigrate. © 2005 Elsevier Ltd. All rights reserved.
Keywords: GEOBASE Subject Index: migration determinant; skilled labor; EMTREE medical terms: administrative personnel; controlled study; cultural factor; female; Ghana; human; interview; male; medical school; migration; Nigeria; physician; policy; resident; review; student; MeSH: Emigration and Immigration; Focus Groups; Foreign Medical Graduates; Ghana; Great Britain; Health Policy; Humans; Interviews; Nigeria; United States